SOCIALIZATION OF MENTAL HEALTH FOR PREGNANT WOMEN THROUGH “HOLDING BY HUSBANDS” IN SUPPORTING A PROSPEROUS PREGNANCY PERIOD - Probowati, Rovica; Buyu Prakoso, Adi (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
Background: Mental health is an important component of overall well-being, especially for pregnant women and has an impact on the fetus. WHO reports that 1 in 5 women will experience mental health problems during pregnancy or one year after giving birth. The impact of mental health problems on mothers will have physical and psychological impacts on both the mother and her baby, such as maternal depression, postpartum depression, and can have an impact on the birth of low birth weight (LBW) babies. Objective: This community service is to socialize the importance of mental health for pregnant women by prioritizing the role of "HOLDING HUSBAND" in maintaining the Welfare of Pregnant Women. This community service is carried out with a descriptive approach using the role of "HOLDING HUSBAND" such as (Support system; Avoid negative things; Positive activities; Time for yourself; Adequate rest). The target of community service is 30 pregnant women in the first, second, and third trimesters who fill out a mental health questionnaire before and after the socialization takes place. Results: Community service shows that there is an increase in maternal mental health before and after socialization by 28%. Conclusion: Based on this, it can be concluded that by providing socialization that prioritizes the role of "HOLDING BY HUSBAND" pregnant women are expected to become prosperous mothers who can improve the mother's mental health by reducing maternal health problems ranging from anxiety to depression.